Administrative Procedure in the Bureau of Land Management - Robert W. Swenson (Washington University Law Quarterly, 1958)
Sweeping demands for reform in the procedure of federal agencies have characterized recent developments in administrative law. In 1955 it was the Hoover Commission and Task Force Reports on Legal Services and Procedures." This was followed by intensive activity in the American Bar Association, culminating in its proposed Administrative Practice Act, administrative code and other bills now before Congress. If these measures become law, federal administrative law will undergo considerable change. The pressure for general reform has tended to obscure the fact that a number of agencies are constantly reviewing their procedural rules in an effort to comply more fully with the letter and spirit of the Administrative Procedure Act of 1946. This may represent a belated recognition of the fact that the APA is, from their point of view, the lesser of two evils. Or, it may represent an honest effort to meet the criticism which various studies have pointed up. At any rate, reform is in the air. No attempt will be made here to evaluate the new proposals. The purpose of this Article is to direct attention to one agency which has revamped its procedure since 1946 with considerable success: the Bureau of Land Management of the Department of Interior. The discussion of Bureau procedure will be limited to mining claims and grazing applications.
Keywords: Administrative procedure